Local effects of depth-dependent water content of ice and snow and firn layers temperature on a conjectured subglacial lake below Amundsenisen Icefield (Svalbard) - Bucchignani, Edoardo; Mansutti, Daniela; Navarro Valero, Francisco José; Otero García, Jaime; Glowacki, Piotr (E.T.S.I. Telecomunicación (UPM), 2013)
It is known that the Amundsenisen Icefield in Southern Spitzbergen (Svalbard achipelago) is temperate with an upper layer of snow and firn. It is an accumulation area and, though ice/water mass balance is clearly subject to time evolution, observation data on the long-term elevation changes over the past 40 years (Nuth et al., 2010) allow to assume constant icefield surface. Within our study of the plausibility of a subglacial lake (Glowacki et al., 2007), here, we focus on the sensitivity of the system to the thermal effect of the firn and snow layers.